Combustion monitoring system - Yuvan, Ramadhas; Devarajan, Ramasamy (2021)
Study of combustion process in an internal combustion engine to improve the performance of the engine. Flame speed is used to study the stability of combustion process in the engine. A simplified setup of a non compressed air-gas(LPG) mixture is used in this project . The Idea is to determine the flame speed of the combustion dependent on the Fan speed Ion sensor is used to measure the flame speed.The experimental result is compared with the theoretical book value.